Paddle-to-Podium: a four-phased applied research model, translating research into practice for female surfers - Parsonage, J.; MacDonald, M.; Shephard, M.; Gosney, S.; Denny, A.; Minahan, C. (Frontiers in Sports and Active Living, 2025)
The announcement of Teahupo`o, Tahiti as the location for surfing events at the Paris 2024 Olympic Games prompted a focus on performance research specific to female surfers. Following a 14-year absence of competitive female surfing at Teahupo`o, athletes and coaches expressed concerns about safety and wellbeing due to the physical and technical demands of sprint-paddling into such challenging and dangerous waves. This paper presents a methodological research approach designed to address these critical performance challenges in the lead up to the Paris 2024 Olympic Games. The "Paddle-to-Podium" project aimed to enhance sprint-paddling performance in elite Australian female surfers, with the dual objectives of improving wave-riding performance and ensuring athlete safety during the event. A collaborative partnership was formed between Surfing Australia, Griffith University, the Queensland Academy of Sport, and the Australian Institute of Sport to establish a multidisciplinary team committed to supporting Australia`s Olympic success in elite female surfing. The team implemented a four-phase applied research model to bridge the gap between scientific insights and practical application within the daily training environment, ensuring timely and impactful high-performance outcomes. The four phases were: (1) Explore current perceptions of sprint-paddling performance among elite female surfers, (2) Examine key stroke characteristics that contribute to superior sprint-paddling velocity, (3) Execute a tailored technique intervention to optimize sprint-paddling performance, and (4) Sustain research practices to provide a legacy for elite female surfing in Australia.